De Prunner’s Ringlet Erebia triaria (de Prunner, 1798) (Lepidoptera: Nymphalidae: Satyrinae) – a new species for the Republic of Macedonia - Nikola Micevski (Natura Sloveniae)
A single male of de Prunner’s Ringlet Erebia triaria (de Prunner, 1798) was discovered in the lower part of the Jadovska River Valley, near the Selce village in NW part of Macedonia. This is the first record for Macedonia and only the fourth in the Balkan Peninsula, where it is extremely local. This moves the southeasternmost distribution border of the species for about 120 km. This discovery brings the number of butterfly species for Macedonia to 206